2021
DOI: 10.3389/fonc.2021.804685
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Mannitol on Cisplatin-Induced Nephrotoxicity: A Systematic Review and Meta-Analysis

Abstract: IntroductionCisplatin, a chemotherapeutic drug, is widely used for the treatment of various malignant tumors with good effects. However, cisplatin-induced nephrotoxicity is a major dose-limiting factor and a significant adverse event. Mannitol is used to reduce cisplatin-induced nephrotoxicity, which is controversial. This study aimed to evaluate the efficacy and safety of a hydration regimen containing mannitol against cisplatin-induced nephrotoxicity through a meta-analysis.MethodsPotential records from PubM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 81 publications
0
5
0
1
Order By: Relevance
“…Mannitol was an effective and safe drug to reduce cisplatin‐induced nephrotoxicity events, which had a better effect on gastrointestinal and urinary tract cancers 31 . Maltitol is a disaccharide alcohol that is produced by hydrogenation of maltose, and stimulated transepithelial diffusional calcium transfer in the ileum 32 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mannitol was an effective and safe drug to reduce cisplatin‐induced nephrotoxicity events, which had a better effect on gastrointestinal and urinary tract cancers 31 . Maltitol is a disaccharide alcohol that is produced by hydrogenation of maltose, and stimulated transepithelial diffusional calcium transfer in the ileum 32 .…”
Section: Discussionmentioning
confidence: 99%
“…30 Mannitol was an effective and safe drug to reduce cisplatin-induced nephrotoxicity events, which had a better effect on gastrointestinal and urinary tract cancers. 31 Maltitol is a disaccharide alcohol that is produced by hydrogenation of maltose, and stimulated transepithelial diffusional calcium transfer in the ileum. 32 Linoleic acid derivative 13(S)-hydroxyoctadecadienoic acid (13(S)-HODE) was concomitant with increased NF-κB activity, 33 and was closely related to non-small-cell lung cancer, 34 breast cancer, 35 and colon cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al [ 38 ] recently published the results of a meta-analysis of four randomized control trials and seven case-control studies involving 4,168 patients. The results indicated that mannitol causes more nausea/vomiting events and deteriorates renal function in patients with diabetes or hypertension; however, it had the best effect when ≥25 g in total or cisplatin <75 mg/m 2 was administered and might have a better effect on gastrointestinal and urinary tract cancers.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…To further test the potential protective properties of FeS preconditioning, its ability to mitigate cisplatin nephrotoxicity was assessed. Given that significant nephrotoxicity occurs in ~30% of cisplatin‐treated patients (Li et al, 2021 ), FeS mediated renal preconditioning could find substantial clinical application. As shown in the bottom panels of Figure 3 , within 3 days of cisplatin (CP) injection, severe AKI was observed in non‐preconditioned mice (Zager et al, 2021 ).…”
Section: Iron Sucrose: a Trigger For Oxidant Preconditioning And Indu...mentioning
confidence: 99%